2001
DOI: 10.1111/j.1095-8649.2001.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption of East Siberian cod: no support for the metabolic cold adaptation theory

Abstract: Standard metabolic rate (R S ) at 2 C of eight East Siberian cod Arctogadus borisovi, caught in West Greenland, body mass of 601·5 147·6 g (mean ..), was 40·9 5·9 mg O 2 kg 1 h 1 and 59·0 6·6 mg O 2 kg 1 h 1 when extrapolated to a standardized 100 g fish. R S was compared with three other Gadidae, to test the theory of metabolic cold adaptation (MCA). There was no evidence of MCA in the family. 2001 The Fisheries Society of the British Isles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Since its introduction the MCA concept has been vigorously discussed in the literature. While most studies support higher activity rates for enzymes associated with energy metabolism in species from polar regions (Hochachka 1988;Crockett and Sidell 1990;West et al 1999;Kawall et al 2002a) (but also see Magnoni et al 2013), experimental results deviate widely at the whole-organism level (Holeton 1974; Torres and Somero 1988;Clarke and Johnston 1999;Jordan et al 2001;Steffensen 2002;White et al 2012). Our results agree well with a recent analysis by White et al (2012), who found evidence for MCA at different levels of organisation in fish, with strongest support at the level of whole-animal metabolic rate.…”
Section: Discussionsupporting
confidence: 87%
“…Since its introduction the MCA concept has been vigorously discussed in the literature. While most studies support higher activity rates for enzymes associated with energy metabolism in species from polar regions (Hochachka 1988;Crockett and Sidell 1990;West et al 1999;Kawall et al 2002a) (but also see Magnoni et al 2013), experimental results deviate widely at the whole-organism level (Holeton 1974; Torres and Somero 1988;Clarke and Johnston 1999;Jordan et al 2001;Steffensen 2002;White et al 2012). Our results agree well with a recent analysis by White et al (2012), who found evidence for MCA at different levels of organisation in fish, with strongest support at the level of whole-animal metabolic rate.…”
Section: Discussionsupporting
confidence: 87%
“…All the fish were deprived of food for 48-h prior to entering the chambers to ensure a complete gastric evacuation. We allowed them an additional 15-h acclimation period inside the chambers before measuring oxygen consumption, a settling time that has been found to be enough to ensure that the fish have stabilized at a steady rate of oxygen consumption (see Drud Jordan et al, 2001). The fish were kept in darkness and always remained quiescent throughout the trials.…”
Section: Metabolic Ratesmentioning
confidence: 99%
“…Single fish were introduced into a perspex circular arena respirometer (diameter 41.0 cm, height 11 cm, volume 14.2 l; Steinhausen 2005; Fig. 1) after being left to acclimatize for minimum of 6 h. This period appeared to be sufficient for other fish to settle to a routine oxygen consumption rate (Steffensen et al 1984;Jordan et al 2001). The respirometer was submerged in water to keep the temperature constant at 13°C.…”
Section: Respirometry Of Spontaneous Swimmingmentioning
confidence: 99%